Reflector-Backed Antenna for UWB Medical Applications with On-Body Investigations - Chaïmaâ Kissi; Mariella Särestöniemi; Timo Kumpuniemi; Sami Myllymäki; Marko Sonkki; Mohamed Nabil Srifi; Heli Jantunen; Carlos Pomalaza-Raez (International Journal of Antennas and Propagation)
A recent reflector-backed antenna model is proposed in this paper for wireless capsule endoscopy localization. The antenna is designed to operate at the lowest 802.15.6 mandatory UWB (ultrawideband) channel, i.e., 4 GHz center frequency with 500 MHz bandwidth. The antenna achieves a good directivity and radiates well over the frequency band of interest. The proposed antenna was constructed within three successive steps. Initially, a planar omnidirectional antenna was designed of 3.15 dBi gain at 4 GHz. Since the antenna aims to operate as a receiving antenna, good directivity is preferred. Thus, an air-filled cavity was included backing the planar antenna to bolster the directivity toward the radiating element. The cavity-backed antenna has a measured gain of 6.4 dBi. The antenna was evaluated next to the homogenous and multilayer models. Then, the antenna design was optimized, by reducing its size, to a reflector-backed antenna structure reaching a maximum gain of 5.3 dBi, which is still promising for the regarded application. The body effect on the antenna matching was evaluated by means of multilayer and voxel models simulating the human body. This was followed by on-body measurements involving real subject. The depth of in-body propagation, from skin to small intestine, was studied using the multilayer and voxel models. Simulations were run using the CST Microwave Studio tool. While prototyping, free-space and on-body measurements took place at University of Oulu, Finland.